Carbon-isotope stratigraphy recorded by the Cenomanian-Turonian Oceanic Anoxic Event: correlation and implications based on three key localities (Geological Society Publishing House on behalf of the Geological Society of London, 2004)

(untitled)
We present new, detailed carbon-isotope records for bulk carbonate, total organic carbon (TOC) and phytane from three key sections spanning the Cenomanian–Turonian boundary interval (Eastbourne, England; Gubbio, Italy; Tarfaya, Morocco), with the purpose of establishing a common chemostratigraphic framework for Oceanic Anoxic Event (OAE) 2. Isotope curves from all localities are characterized by a positive carbon-isotope excursion of c. 4 for TOC and phytane and c. 2.5 for carbonate, although diagenetic overprinting appears to have obliterated the primary carbonate carbon-isotope signal in at least part of the Tarfaya section. Stratigraphically, peak 13C values for all components are followed by intervals of high, near-constant 13C in the form of an isotopic plateau. Recognition of an unambiguous return to background 13C values above the plateau is, however, contentious in all sections, hence no firm chemostratigraphic marker for the end-point of the positive isotopic excursion can be established. The stratigraphically consistent first appearance of the calcareous nannofossil Quadrum gartneri at or near the Cenomanian–Turonian boundary as established by ammonite stratigraphy, in conjunction with the end of the 13C maximum characteristic of the isotopic plateau, provides a potentially powerful tool for delimiting the stratigraphic extent and duration of OAE 2. This Oceanic Anoxic Event is demonstrated to be largely, if not wholly, confined to the latest part of the Cenomanian stage.